Evaluation of a novel osteosynthesis plate system for mandibular defects. Issue 9 (November 2020) - Peters, F.; Kniha, K.; Möhlhenrich, S.C.; Bock, A.; Hölzle, F.; Modabber, A.
Abstract: Continuity defects of the jaw can be reconstructed with titanium plates or microvascular bone flaps; osteosynthesis plates are necessary for both. In this study we performed a retrospective review of patients treated with Medartis MODUS® Mandible Trauma/Reco 2.0-2.5, TriLock bridging plates, mandibulectomy and soft tissue free flap or reconstruction with a bony free flap and TriLock mandibular plates from the same system from January 2015 to August 2019. The variables recorded were sex, age, diagnosis, radiotherapy, date of implantation, date of explantation or death of patient, size of mandibular defect, Jewer classification of defect, number of screws used, segments of bony reconstruction, screws per segment, plate exposure, plate breakage, and pseudarthrosis. The bridging plate group consisted of 41 patients, while the mandibular plate group consisted of 24 patients. The percentage of plate exposure was 17.07% for the bridging plate group and 4.17% for the mandibular plate group. Plate breakage was 0 in both groups. Pseudarthrosis was 4.17% in the mandibular plate group. In the bridging plate group, an anterolateral thigh flap covered all exposures. Of 7 plate exposures, 4 were found in a C defect. The complication rate of the investigated plates was lower than the complication rates of other plate systems.